2018
DOI: 10.1186/s13071-018-2988-0
|View full text |Cite
|
Sign up to set email alerts
|

Host-parasite interaction: changes in human placental gene expression induced by Trypanosoma cruzi

Abstract: BackgroundChagas disease is caused by Trypanosoma cruzi, a parasite endemic to Latin America. Most infections occur in children by vector or congenital transmission. Trypanosoma cruzi establishes a complexity of specific molecular parasite-host cell interactions to invade the host. However, most studies have been mainly focused on the interaction between the parasite and different cell types, but not on the infection and invasion on a tissue level. During congenital transmission, T. cruzi must cross the placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
5
26
1
Order By: Relevance
“…Although Castillo et al (2018) previously reported changes similar to those described in the present model, the number of downregulated genes was high compared with that observed by Chiribao et al (2014). That study found a high number of differentially expressed genes (1700) when the effect of infection on epithelial cells was analyzed.…”
Section: Discussionsupporting
confidence: 55%
“…Although Castillo et al (2018) previously reported changes similar to those described in the present model, the number of downregulated genes was high compared with that observed by Chiribao et al (2014). That study found a high number of differentially expressed genes (1700) when the effect of infection on epithelial cells was analyzed.…”
Section: Discussionsupporting
confidence: 55%
“…Pathogens have evolved strategies to exploit resources from their hosts to maximize their own survival, replication, and dissemination. Thus, different kinds of pathogens (including (16,32,33). Both of the parasites studied here are able to manipulate host gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the congenital isolates were highly invasive into spheroids, in contrast with the isolate obtained from a mother, which after delivered several children never transmitted the infection to her offspring, which showed a low/moderate transmigration ability. T. cruzi congenital transmission is the result of a complex interaction between trypomastigotes and the placental barrier [5052]. Recently, Juiz et al (2017) described a differential placental gene response induced by strains with different tropism and virulence.…”
Section: Discussionmentioning
confidence: 99%